Investigation on the structural feature and gasification reactivity of bio-char derived from energy crop. (1st April 2021) - Liu, Yun; Zhang, Yuan; Zhang, Yu-qing; Chen, Lian-sheng; Li, Hai-ying; Liu, Hui-min
Abstract: A kind of energy crops ( Arundo donax ) was selected to investigate effects of pyrolysis heating rate (PHR) on char structure and CO2 gasification reactivity. The gasification reactivity and microstructure of char obtained at various PHR were explored. Besides, the surface morphology, microcrystalline and aromatic structure of bio-chars were analyzed via scanning electron microscopy, X-ray diffraction, and Raman spectroscopy. The results reveal that the main thermal decomposition of Arundo donax occurs in the range of 180 °C - 570 °C. The surface of chars obtained at rapid pyrolysis appears to be rougher than that under slow pyrolysis. Rapid pyrolysis results in high temperature gradient inside and outside the particles, leading to condensation of free radical fragments in a short time. The bio-char obtained at rapid heating rate has more structural defects and imperfections of the carbon crystallites. Besides, the crystallization size, graphitization and aromatization degree decrease of bio-char were inhibited as the PHR increased. In addition, some H2 O-soluble K was volatilized with the increase of heating rate, and a small part was converted to NH4 Ac-soluble K during pyrolysis. Therefore, the gasification reactivity of chars obtained from rapid pyrolysis rate was higher than that from the low pyrolysis rate, which was associated with the formation of alkali metal distribution and micro-areas structure evolution in the bio-chars.